l-Fucose residues on cellulose-based dialysis membranes: Quantification of membrane-associatedl-fucose and analysis of specific lectin binding - Meißner, Carsten; Deppisch, Reinhold; Hug, Friederike; Schulze, Matthias; Ritz, Eberhard; Ludwig, Horst; Hänsch, Gertrud Maria (Glycoconjugate journal, 1995)
Contact of mononuclear human leukocytes with cellulose dialysis membranes may result in complement-independent cell activation, i.e. enhanced synthesis of cytokines, prostaglandins and an increase in β2-microglobulin synthesis. Cellular contact activation is specifically inhibited by the monosaccharidel-fucose suggesting that dialysis membrane associatedl-fucose residues are involved in leukocyte activation. In this study we have detected and quantitatedl-fucose on commercially-available cellulose dialysis membranes using two approaches. A sensitive enzymatic fluorescence assay detectedl-fucose after acid hydrolysis of flat sheet membranes. Values ranged from 79.3±3.6 to 90.2±5.0 pmol cm−2 for Hemophan® or Cuprophan® respectively. Enzymatic cleavage of terminal α-l-fucopyranoses with α-l-fucosidase yielded 7.7±3.3 pmoll-fucose per cm2 for Cuprophan. Enzymatic hydrolysis of the synthetic polymer membranes AN-69 and PC-PE did not yield detectable amounts ofl-fucose. In a second approach, binding of the fucose specific lectins ofLotus tetragonolobus andUlex europaeus (UEAI) demonstrated the presence of biologically accessiblel-fucose on the surface of cellulose membranes. Specific binding was observed with Cuprophan®, and up to 2.6±0.3 pmoll-fucose per cm2 was calculated to be present from Langmuir-type adsorption isotherms. The data presented are in line with the hypothesis that surface-associatedl-fucose residues on cellulose dialysis membranes participate in leukocyte contact activation.